Xanthogranulomatous Pyelonephritis of a Lower Pole Moiety in a Duplicated Collecting System Kidney. (8th September 2015) - Wuilleumier, Jean Paul; Schulman, Ariel; Montgomery, Antonio; Teper, Ervin
Abstract : Xanthogranulomatous pyelonephritis (XGP) is a destructive inflammatory process which is frequently caused by recurrent urinary tract infections or chronic obstruction by kidney stones. We present a 56-year-old female with an extensive retroperitoneal urinoma and xanthogranulomatous pyelonephritis of the lower pole moiety in a kidney with a duplicated collecting system due to obstructive nephrolithiasis. After drainage of the urinoma, the patient underwent a definitive lower pole heminephrectomy with preservation of the functional upper pole. We review important clinical features of xanthogranulomatous pyelonephritis and considerations for surgery on a duplicated kidney.